Penatalaksanaan Hiperurisemia Pada Penyakit Ginjal Kronik (CKD) - Haidar Alatas (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Management of hyperuricemia in CKD includes non pharmacology and pharmacology. Non-pharmacological with lifestyle change interventions such as exercise, weight loss, low purine meat consumption, avoid high fructose, reduce alcohol and herbs. The treatment of asymptomatic hyperuricemia in CKD is still controversial. In Japan and Korea given uric acid-lowering drugs when the serum uric acid level (SUA)> 8 mg / dl but in America and Europe are not given drugs for fear of side effects. Soursop fruit consumption can be an alternative treatment for hyperuricemia in CKD both asymptomatic and symptomatic. The recommended drugs for hyperuricemia in CKD are allopurinol and febuxostat. Allopurinol is excreted through the kidneys so it is necessary to adjust the dose in CKD, starting from 50-100 mg / day, increasing it to 200-300 mg / day every 2-5 weeks until SUA <6 mg / dl. The dose may be> 300 mg / day if the patient is notified and the monitor may be toxic. In America, Europe and Japan recommend febuxostat only for the treatment of hyperuricemia.